2018
DOI: 10.1097/iae.0000000000001898
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Internal Limiting Membrane Flap Technique for Treatment of Macular Hole Retinal Detachment in Highly Myopic Eyes

Abstract: The inverted ILM flap technique with the presence of bridging tissue over the MH is effective in closing the MH and improving the postoperative best-corrected visual acuity in eyes with MH retinal detachment by bridging tissue over the MH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 27 publications
0
37
0
1
Order By: Relevance
“…Kumar and Yadav [23] considered that the tissue pillars could be composed of redundant retinal tissue, subclinical epiretinal membranes, or small residual pieces of the ILM attached to the edges of the hole. They suggested that the mechanism of closure could be similar to the inverted ILM flap surgical approach in which the pillars provide mechanical support to bridge the gap and more quickly cover up the defects in the inner retina [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Kumar and Yadav [23] considered that the tissue pillars could be composed of redundant retinal tissue, subclinical epiretinal membranes, or small residual pieces of the ILM attached to the edges of the hole. They suggested that the mechanism of closure could be similar to the inverted ILM flap surgical approach in which the pillars provide mechanical support to bridge the gap and more quickly cover up the defects in the inner retina [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the heterogeneity was low. is may be attributed to the study of Takahashi et al [29], who reported a lower postoperative retinal reattachment rate for the inverted ILM flap group.…”
Section: Discussionmentioning
confidence: 92%
“…However, there was a significant intergroup difference in the postoperative BCVA at 12 months after surgery, with no heterogeneity. is could be attributed to the use of BBG for ILM staining in all three included studies [28][29][30]. Glial cell proliferation induced by the inverted ILM flap, as proposed by Michalewska, produces an environment for photoreceptors to assume new positions in direct proximity to the fovea, thus resulting in improved postoperative visual acuity [16].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They suggested that the mechanism of closure could be similar to the inverted ILM flap surgical approach in which the pillars provide mechanical support to bridge the gap and more quickly cover up the defects in the inner retina. [24][25][26][27] Visual recovery after MH closure may depend on the recovery of the retinal microstructure in the fovea, particularly the outer retina. [5][6][7][8] The authors reported that the restoration of the ELM and the EZ lines over the closed MH was associated with better BCVAs.…”
Section: Discussionmentioning
confidence: 99%